Chemical sensitivity of Mo gate MOS capacitors - R.M. Lombardi (Revista Mexicana de Física, 2006)
Mo gate MOS capacitors exhibit a negative shift of their C–V characteristic by up to 240 mV, at 125°C, in response to 1000 ppm hydrogen, in controlled nitrogen atmospheres. The experimental methods for obtaining capacitance and conductance, as a function of polarisation voltage, as well as the relevant equivalent circuits are reviewed. The single–state interface state density, at the semiconductor–dielectric interface, decreases from 2.66 1011 cm–2e–v–1, in pure nitrogen, to 2.5 1011cm–2e–v–1 in 1000 ppm hydrogen in nitrogen mixtures, at this temperature.